COMPARISON OF OFFSET PRINTING INK QUALITY ON THE MARKET - Romi Kusbani; Tedy Taviantoa; Yessy Yerta Situngkir; Mawan Nugraha (Politeknik Negeri Media Kreatif, 2019)
Ink quality study have been observed on ink products in the market as a right confirmation of ink users for printint production. The study is also conducted to ensure the suitability of the ink with the printing materials and machines used by consumers. The observation was conducted on two brands of ink from the same manufacturer. The quality data studied were viscosity, spreadability, drying time, density and L*a*b. The results show that, although both inks are produced by the same manufacturer and are intended for the same market, there are differences in quality, namely one has a higher viscosity and a faster drying time than the other.Keywords—quality of printing ink, viscosity, spreadability, drying time, density and L*a*b